Consumer Counting System in Stores Based on Internet of Things (IoT) With ESP 32 Microcontroller and Ultrasonic Distance Sensor - Setiawan, Hiskia Kus; Rudi Susanto; Pramono (LPPM Telkom University Surabaya, 2024)
In the era of modern technology, efficiency and accuracy in store management have become very important. This research aims to develop an Internet of Things (IoT) based consumer counting system using an ESP32 microcontroller and an ultrasonic distance sensor. This system is designed to help shop owners monitor the number of consumers who come so they can improve stock management and services. The research method used is a prototype, starting from needs analysis, system design, and prototyping to implementation and testing. The research results show that this system is able to detect consumers with high accuracy; the 1% error that researchers got was because the ultrasonic sensor was delayed and displayed the number of consumers on the I2C LCD screen as well as the Blynk IoT application. This system is expected to provide practical solutions for shop owners to optimize shop operations.